Screening of nutrients for the productive of Myco-coagulant from Lentinus squarrosulus for water treatment - Hassan, Hamidah; Alam, Md. Zahangir; Al-Mamun, Abdullah; Mujeli, Mustapha (EM International, 2021)
Chemical coagulants have been continuously used for the treatment of water turbidity and suspended solids despite their harmful consequences on living beings. These problems obliged scientists in various parts of the world to investigate eco-friendly novel technologies. In this regard, a new Myco-coagulant is successfully produced by a group of researchers at the Bioenvironmental Engineering Research Centre of International Islamic University Malaysia. The present study assessed the nutrients level required to culture a previously isolated fungus from river water known as Lentinus squarrosulus. Synthetic water using kaolin suspension was prepared and used to study the removal of turbidity by the cultured Myco-coagulant using the flocculation mechanisms. Thus, the paper reported the experimental findings on nutrient screening and optimization of the suitable growth conditions and production of the fungus Myco-coagulant. The growth media that showed positive effects on the fungus growth according to Plackett–Burman design were yeast extract (11.2%), malt extract (6.0%), inoculum size (3.5%), and glucose (3.0%). However, agitation speed (-12.17%) had the most negative influence on Myco-coagulant growth, followed by urea (-7.67). Other growth conditions with negative effects includes; pH (-5.8%), culture time (-5.5%), and CaCl2 (-5.0%). Nevertheless, yeast extract and agitation speed were selected as the major parameters for fungus growth optimization. In conclusion, the submerged fermentation of Lentinus squarrosulus using yeast extract as a nutrient demonstrates a better yield than malt extract. Moreover, urea and CaCl2 could be excluded from the nutrient composition because of their insignificant contribution to fungal growth.